Digestibilidade de alimentos protéicos e energéticos para kinguio (Carassius auratus) - Raphael Nogueira Bahiense (2017)
This work aimed to determine the digestibility of protein and energy ingredients for goldfish (Carassius auratus). A total of 150 animals (5.0 ± 1.0 g, on average) were used, distributed in six aquariums (20 L each), with two aquariums replicating. Seven treatments with three replicates. The treatments applied were: Ref: diet reference; Sor: diet based on sorghum; Tri: base diet with wheat; Arr: diet based on rice; Ami: base diet with corn starch; Soj: diet based on soybean meal; Fpn: base diet with national fish meal. The animals underwent adaptation of four days, receiving the diets. The collected feces were dried in an oven for analysis of dry matter, crude protein, crude energy and chromium oxide. The data were submitted to ANOVA and the means were compared by the Tukey test (5%). The apparent digestibility coefficients (CDA) of the dry matter (DM) of the animals fed sorghum, wheat, rice and corn starch (60.83, 64.72, 65.15, 63.87%, respectively) were similar ( P> 0.05); the animals fed with the diet containing wheat had better results for crude protein (CP) (80.75%) (p <0.05); the crude energy CDA values were similar for rice (77.46%) and maize starch (77.01%) (p> 0.05). The apparent digestibility coefficients of the ingredient (CDAi) of DM were not influenced by the energy sources wheat, rice and corn starch (79.70, 81.14, 76.88%, respectively) (p> 0.05); the CDAi CP of the fish fed diet with wheat (98.83%) was higher than the other, and fed with rice and corn starch showed CDAi the best CE (100; 99.37%, respectively) (p <0.05). Protein ingredients tested did not influence the DM CDA of goldfish (p> 0.05). The diets formulated with soybean meal and national fish meal provided higher CDA (79.69, 76.86%, respectively), when compared to the reference diet (74.44%) (p <0.05). The diets with soybean meal and national fish meal determined similar CDA for CE (77.48; 77.18%, respectively) (p> 0.05); However, fish fed with soybean meal showed better CDAi of MS (71.91%) (p <0.05). The CDAi of CP of the goldfish that received soybean meal in the diet was higher than the other protein ingredients (91.92%) (p <0.05) and for the ADC CD of these foods, no significant difference was found (p> 0.05). It is concluded that in the experimental conditions proposed, the goldfish presented better energy utilization in diets formulated with rice and maize starch. Diets with up to 30% of soybean meal are assimilated more efficiently by goldfish, compared to those formulated with imported fishmeal as a protein source.